2019
DOI: 10.1177/0258042x18822564
|View full text |Cite
|
Sign up to set email alerts
|

Role of Career Adaptability and Its Resources in Predicting Vocational Attitudes of Indian IT Professionals

Abstract: Indian Information Technology (IT) market is going through a dynamic state of existence with employment uncertainties, but simultaneously creating promising opportunities. Amidst such unpredictability and possibilities, Indian IT professionals have been striving hard to build a career identity, demonstrating their capabilities to withstand unforeseen and abrupt vocational shocks. In career construction, such capability comes from career adaptability, reflected through resources of concern, control, curiosity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
1
0
0
1
Order By: Relevance
“…Previous research has shown that perceived career management can promote employee job-related attitudes by increasing positive evaluation and expectations of their career development (De Vos et al, 2009;Guan et al, 2014). In line with the results of previous studies, Santra & Giri (2019) and Seibert & Kraimer (2001) concluded that perceived career management would increase individual career satisfaction and can reduce turnover intention (employee intention to leave their organization). Based on the description above, the hypothesis can be formulated as follows.…”
Section: Mediation Effect Of Cs On the Relationship Between CM And Tisupporting
confidence: 64%
“…Previous research has shown that perceived career management can promote employee job-related attitudes by increasing positive evaluation and expectations of their career development (De Vos et al, 2009;Guan et al, 2014). In line with the results of previous studies, Santra & Giri (2019) and Seibert & Kraimer (2001) concluded that perceived career management would increase individual career satisfaction and can reduce turnover intention (employee intention to leave their organization). Based on the description above, the hypothesis can be formulated as follows.…”
Section: Mediation Effect Of Cs On the Relationship Between CM And Tisupporting
confidence: 64%
“…Karatepe menjelaskan bahwa tidak adanya hubungan career adaptability dan job hopping intention karena career adaptability dinilai sebagai kemampuan problem solving untuk permasalahan yang dihadapi sehari-hari sehingga tidak memungkinkan untuk karyawan untuk pindah pekerjaan. Hal ini senada dengan penelitian Santra yang menjelaskan bahwa karyawan IT di India akan meninggalkan pekerjaan jika mereka mendapatkan peluang yang tepat dan memikirkan masa depannya (Santra & Giri, 2019).…”
Section: Diskusiunclassified